Recent Acquisitions. - Galerie Rudolf Zwirner, Köln; Galleria Paolo Sprovieri, Roma (Roma : Galleria Paolo Sprovieri)
André ; Arp ; Balla ; Burri ; Brauner ; De Chirico ; Dine ; Dubuffet ; Ernst ; Fautrier ; fontana ; Kandinsky ; Klee ; Kline ; Leger ; Lichtenstein ; Magritte ; Miro ; Oldenburg ; Picabia ; Pollock ; Rauschenberg ; Riopelle ; Ryman ; Rothko ; Tanguy ; Tapies ; Twombly
Recent Acquisitions, Galleria Paolo Sprovieri, Roma ; Galerie Rudolf Zwirner, Köln, [1986]
Engels & Frans
kunstcatalogus